2006
DOI: 10.1124/dmd.106.010587
|View full text |Cite
|
Sign up to set email alerts
|

CYP4F Enzymes Are the Major Enzymes in Human Liver Microsomes That Catalyze the O-Demethylation of the Antiparasitic Prodrug DB289 [2,5-Bis(4-amidinophenyl)furan-bis-O-methylamidoxime]

Abstract: DB289 [2,5-bis(4-amidinophenyl)furan-bis-O-methylamidoxime] is biotransformed to the potent antiparasitic diamidine DB75 [2,5-bis(4-amidinophenyl) furan] by sequential oxidative O-demethyl-ation and reductive N-dehydroxylation reactions. Previous work demonstrated that the N-dehydroxylation reactions are catalyzed by cytochrome b 5 /NADH-cytochrome b 5 reductase. Enzymes responsible for catalyzing the DB289 O-demethylation pathway have not been identified. We report an in vitro metabolism study to characterize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
88
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 79 publications
(94 citation statements)
references
References 35 publications
4
88
1
Order By: Relevance
“…It should be noted that the reverse biotransformations are also possible, at least in vitro, since the dicationic amidine, diminazene (which also possesses antitrypanocidal properties) is known to undergo two successive N-oxidation reactions: first to the mono-oxime and then to the di-oxime (Clement et al, 1992). The metabolic conversion of DB289 to DB75 in vitro using isolated rat hepatocytes consists of sequential oxidative O-demethylation and reductive N-dehydroxylation reactions (Zhou et al, 2004), and it has been demonstrated recently that hepatic CYP4F enzymes, including CYP4F2 and CYP4F3B, catalyze the initial O-demethylation of DB289 in humans (Wang et al, 2006). Pentamidine is metabolized in vitro mainly by multiple phase I cytochrome P450-induced side-chain C-hydroxylation reactions, but its minor biotransformation pathways involve N-hydroxylation to the oximes (Berger et al, 1990a(Berger et al, ,b, 1991(Berger et al, , 1992Clement and Jung, 1994).…”
Section: Discussionmentioning
confidence: 99%
“…It should be noted that the reverse biotransformations are also possible, at least in vitro, since the dicationic amidine, diminazene (which also possesses antitrypanocidal properties) is known to undergo two successive N-oxidation reactions: first to the mono-oxime and then to the di-oxime (Clement et al, 1992). The metabolic conversion of DB289 to DB75 in vitro using isolated rat hepatocytes consists of sequential oxidative O-demethylation and reductive N-dehydroxylation reactions (Zhou et al, 2004), and it has been demonstrated recently that hepatic CYP4F enzymes, including CYP4F2 and CYP4F3B, catalyze the initial O-demethylation of DB289 in humans (Wang et al, 2006). Pentamidine is metabolized in vitro mainly by multiple phase I cytochrome P450-induced side-chain C-hydroxylation reactions, but its minor biotransformation pathways involve N-hydroxylation to the oximes (Berger et al, 1990a(Berger et al, ,b, 1991(Berger et al, , 1992Clement and Jung, 1994).…”
Section: Discussionmentioning
confidence: 99%
“…Results indicated that members of the CYP4F subfamily, including CYP4F2 and CYP4F3B, were the primary catalysts of this reaction (Wang et al, 2006). However, M1 formation rates in the panel of HLM varied only 4-fold (Wang et al, 2006). Thus, if this reaction is the rate-limiting step in the biotransformation of DB289, then variation in hepatic metabolism may have a minor contribution to the variation in the systemic exposure of DB289.…”
mentioning
confidence: 98%
“…Results indicated that members of the CYP4F subfamily, including CYP4F2 and CYP4F3B, were the primary catalysts of this reaction (Wang et al, 2006). However, M1 formation rates in the panel of HLM varied only 4-fold (Wang et al, 2006).…”
mentioning
confidence: 99%
See 2 more Smart Citations